Classical and exotic magnetism: recent advances and perspectives - Kivshar, Y.; Roberts, A.P. (Физика низких температур, 2017)
Motivated by the pioneering studies of Eremenko of magneto-optical effects in antiferromagnetic crystals, we describe an expansion of the horizons of classical magnetism to include study of Earth's magnetic field and natural environments. We also review briefly examples of exotic magnetism not directly associated with alignment of quantum spins in traditional ferromagnetic and antiferromagnetic crystalline structures. While many such cases have long been known, recent breakthroughs are associated with so-called optical magnetism that became a reality due to development of the field of metamaterials.